Quantifying Street Tree Regulating Heat Effects Using a Generalized Linear Mixed Model Approach - Rosos Djikpo, V. A.; Teka, Oscar; Abalo, Sandrine; Hozanhekpon, Murielle; Noudehou, Ghislaine; Sinsin, Brice (European Scientific Journal, ESJ, 2023)
Climate change has emerged as a significant global environmental concern, prompting increased interest in utilizing trees as an alternative means to enhance human well-being and thermal comfort in urban settings. This study endeavors to assess the influence of street trees on the urban microclimate in tropical cities, employing a Generalized Linear Mixed Model (GLMM) approach. The investigation was carried out in Cotonou, Porto-Novo, and Ouidah within Benin. Data collection was conducted along thoroughfares, where a systematic inventory was performed to measure various characteristics of each street tree, including crown shape, shade form on the ground, crown diameter, diameter at breast height, and tree height. Meteorological data, encompassing air temperature, relative humidity, and wind speed, were recorded at three different heights, thrice an hour from 7 am to 7 pm. Subsequently, these datasets were analyzed using GLMMs. A total of 1127 street trees belonging to 20 species and 13 families were identified. The Shannon Diversity Index and Pielou Equitability values ranged from 2.33 to 2.92 bits and 0.17 to 0.64, respectively. The GLMM analysis revealed that the presence of trees, daytime, and height significantly influenced air temperature, relative humidity, and wind speed. The presence of street trees on both sides of roadways induced an air temperature decrease ranging from -0.6°C to -1.4°C and an increase in relative humidity ranging from +2.5% to +5.2% between 11 am and 5 pm, as compared to other layouts. Furthermore, closed canopy patterns exhibited the most favorable outcomes, resulting in an air temperature decrease ranging from -0.4°C to -1°C and an increase in relative humidity ranging from +2.4% to +5.5% between 11 am and 5 pm. These findings hold the potential to inform urban planners and policymakers in designing and implementing effective street tree planting strategies that optimize cooling effects and mitigate the impact of climate change on urban areas.